EFEK MODERASI KESUKARELAAN TERHADAP PEMBELAJARAN ONLINE PADA UNIVERSITAS SAHID SURAKARTA - Yulius, Rina; Santosa, Paulus Insap; Hartanto, Rudy (Jurnal Ipteks Terapan, 2016)
E-learning is an IT tool that facilitates learning process. In order to optimize its function, e-learning need to be evaluated. There are many indicators on evaluating e-learning such as voluntariness of use. This study aims to evaluate factors that impact the usage of an e-learning system by considering voluntariness of use as moderating factor on e-learning usage. This study uses the UTAUT model that consists of four independent variables (performance expectancy, effort expectancy, social influence, and facilitating condition), two dependent variables (behavioral intention, use behavior), and one moderating variable (voluntariness). Voluntariness is hypothesized to affect the interaction of social influence and behavioral intention. This study uses Structural Equation Modeling (SEM) to validate the concepts and theories about e-learning usageâs factors at Universitas Sahid Surakarta and Moderated Structural Equation Modeling (MSEM) to validate the moderation effect of voluntariness to the interaction of social influence and behavioral intention. From SEM analysis, we can conclude that performance expectancy and effort expectancy positively influence the behavioral intention of e-learning. Meanwhile, from MSEM analysis we can conclude that voluntariness canât moderate the usage of e-learning.Keywords: e-learning; SEM; UTAUT; voluntariness.